Effect of parental intergroup attitudes on children's in-group bias and out-group discrimination - Jelić, Margareta (2008)
The aim of this study was to determine the effect that parents have on their children regarding group identity, in-group bias and out-group discrimination. Research was conducted in a community consisted of two conflicted ethnic groups living together. Children and parents filled in questionnaires separately, using identical codes in order to link their results. Our sample consisted of 369 children, 343 mothers and 316 fathers. Half of the participants were members of the majority group and half of the minority group. We wanted to test the hypothesis that discrimination by ethnicity as well as in-group bias is something that is taught by significant others, predominantly close family members. Further more, we wanted to investigate whether mothers and fathers have different effect on their sons and daughters. Results were analysed on individual and dyadic level and suggest that parental variables, although not crucial, have significant effect on children's in-group bias, out-group discrimination and national identification level. Parents who show more in-group bias and out-group derogation have children who tend to be more biased and who discriminate against members of other ethnic group. The size of the effect is discussed in relation to the type of dyad (regarding the sex of a parent and a child).
Projekt MZOS
ENG